Vytápění rodinného domu biomasou - Vaculík, Jaroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Bakalářská práce pojednává o tématu biomasa, jejím využití, potenciálu a zabývá se problematikou vytápění rodinného domu. Text obsahuje úvod do problematiky, nastiňuje biomasu jako možnou alternativu vytápění domu. Dále představuje její formy a zařízení určená k jejímu spalování. Práce nabízí též návrh řešení vytápění a výpočtu pro modelový dům na konkrétním objektu.

Bachelor´s thesis deals with the topic of biomass, its usage and potential and follow up the problem of heating a family house. The text contains introduction and outlines the biomass as an alternative of heating the house. Then it discusses its forms and devices designed for its combustion. The work also offers design and calculation of heating solutions for a model house on a particular object.
Heating of Family House by Biomass
Keywords: Biomasa; obnovitelný zdroj energie; výroba tepla; vytápění; kotel; Biomass; a renewable source of energy; heat production; heating; boiler